2007
DOI: 10.1007/s00595-007-3578-5
|View full text |Cite
|
Sign up to set email alerts
|

UFT (Tegafur and Uracil) as Postoperative Adjuvant Chemotherapy for Solid Tumors (Carcinoma of the Lung, Stomach, Colon/Rectum, and Breast): Clinical Evidence, Mechanism of Action, and Future Direction

Abstract: UFT (tegafur and uracil) is an oral anticancer drug that has been developed in Japan. Owing to its mild toxicity profile, UFT can be suitable in an adjuvant setting following a complete tumor resection, whereas its direct antitumor effect achieved may be insufficient for advanced unresectable disease. Therefore, a variety of adjuvant chemotherapy trials with UFT have been conducted, and results of well-designed randomized controlled trials have recently shown a survival benefit of postoperative UFT treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 118 publications
1
23
0
Order By: Relevance
“…2A). Tanaka 27 reported a single-institute phase II trial of adjuvant chemotherapy with carboplatin/paclitaxel followed by tegafur and uracil (UFT) for completely resected node-positive (p-stage II-N1 or IIIA-N2) NSCLC. His interim analysis revealed favorable overall and recurrence-free survival of 73% and 49%, respectively, at 3 years, with minimal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Tanaka 27 reported a single-institute phase II trial of adjuvant chemotherapy with carboplatin/paclitaxel followed by tegafur and uracil (UFT) for completely resected node-positive (p-stage II-N1 or IIIA-N2) NSCLC. His interim analysis revealed favorable overall and recurrence-free survival of 73% and 49%, respectively, at 3 years, with minimal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, S-1 shows a potent inhibitory effect on DPD and an enhanced 5-FU concentration can be expected with S-1 administration. 30 Indeed, a large randomized trial in Japan demonstrated that oral S-1 adjuvant chemotherapy prolonged the overall survival of patients with stage II or III gastric cancer who underwent a gastrectomy with an extended (D2) lymph node dissection. 31 However, this trial did not show whether the adjuvant chemotherapy is useful for patients with SGC.…”
Section: Therapeutic Procedures Used To Treat Sgcmentioning
confidence: 99%
“…Recent clinical studies have shown that UFT (a prodrug of 5-FU, Tegafur, combined with uracil in a 1:4 molar ratio) is an active oral chemotherapeutic agent in postoperative adjuvant settings for completely resected early-stage lung, gastric, colorectal, and breast cancer that does not exhibit any remarkable toxicity (2). UFT can achieve a higher maximum plasma 5-FU level for a longer period by inhibiting 5-FU degradation, thereby enhancing its antitumor effect (3).…”
mentioning
confidence: 99%